2022
DOI: 10.1016/j.ejogrb.2022.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Do obstetric units adhere to the evidence-based national guideline? A Germany-wide survey on the current practice of initial tocolysis

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…There have been many similar studies conducted in countries around the world [ 22 ], including in Australia [ 41 ], Austria [ 30 ], Canada [ 42 ], France [ 18 , 43 ], New Zealand [ 41 ], UK [ 44 ], Germany [ 4 ], and USA [ 45 ]. All of these studies found that tocolysis practice patterns varied widely between practitioners and that not all obstetricians prescribed according to scientific evidence, as is the case in Taiwan, and this study attempted to address this concern.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There have been many similar studies conducted in countries around the world [ 22 ], including in Australia [ 41 ], Austria [ 30 ], Canada [ 42 ], France [ 18 , 43 ], New Zealand [ 41 ], UK [ 44 ], Germany [ 4 ], and USA [ 45 ]. All of these studies found that tocolysis practice patterns varied widely between practitioners and that not all obstetricians prescribed according to scientific evidence, as is the case in Taiwan, and this study attempted to address this concern.…”
Section: Discussionmentioning
confidence: 99%
“…Preterm birth is still a major challenge for obstetricians worldwide and is associated with neonatal complications, such as respiratory distress syndrome (RDS), intraventricular hemorrhage (IVH), necrotizing enterocolitis (NE), and retinopathy of prematurity [ 1 , 2 , 3 , 4 , 5 ]. According to the Global Health Observatory by the World Health Organization, complications of prematurity are a leading cause of death under 5 years of age, with 964,366 deaths in 2017 alone, accounting for 17.8% of the under-5-mortality globally [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the most widely used tocolytic is the CCB group, which is nifedipine. It is said that this drug is quite effective in inhibiting the process of preterm labor, with minimal side effects [18] Previous studies have shown the success of nifedipine in preventing preterm labor and relieving contractions in contractile uterine patients reaching 86.4% and reducing pain scale to 74.28% [19]. Other studies have shown that the success rate of nifedipine therapy as a tocolytic in patients with postpartum prematurus imminens at the Prof. Dr. I.G.N.G.…”
Section: The Role Of Mgso4 and Nifedipine As Management Of Prom In Pr...mentioning
confidence: 99%
“…The ACS coverage, for instance, ranges from 16-91% across the world. Moreover, prescribing tocolytics in the clinical setting is often symptom-based rather than strictly conforming to the guideline recommendations [14][15][16][17]. Taken together, the highly heterogeneous pathogenesis and clinical presentation of preterm labor require more exploration into variations of clinical practice.…”
Section: Introductionmentioning
confidence: 99%